MONITORING BUTTERFLY BIODIVERSITY ON PRIME BUTTERFLY AREA Avala Mt. (Serbia) BY THE TRANSECT METHOD (Pollard Walks) IN THE YEAR 2017 - Jakšić, Predrag; Janžekovič, Franc; Klenovšek, Tina (Bulletin of Natural Sciences Research, 2017)
An inventory of butterfly fauna was carried out in 2017 within the north-western part of the Prime Butterfly Area “Avala Mt.”. Butterfly fauna was surveyed with a transect method from March until October within three sectors with different land use and plant succession. We evaluated the sectors by butterfly species richness, abundance of individuals, species accumulation curves, Shannon index, ecological and zoogeographical characteristics. A total of 1147 individuals were recorded, representing 50 species. Three new species (Pieris mannii (Mayer, 1851), Satyrium acaciae (Fabricius, 1787) and Kirinia roxelana (Cramer, 1777)) for the fauna of Avala Mt. were discovered that now counts 114 species. Abandoned dry grasslands in the process of secondary succession supported the highest number of species and individuals. Nevertheless, the observed butterfly species on Avala Mt. were almost equally characteristic for grasslands (38.4%) and forests (34.3%). In conclusion, butterfly biodiversity on Avala Mt. depends on habitat diversity, which is a combination of climax forest vegetation as well as formerly agricultural landscapes in different stages of secondary succession.